Program Edukasi Covid-19 dan Pengenalan Aksara Lontara Kepada Siswa Mts Guppi di Desa Possi Tanah, Kecamatan Kajang, Kabupaten Bulukumba - Iqbal; Mukrimin; jabul reski, fadhil (Departemen Teknologi Pertanian Universitas Hasanuddin, 2021)
Community service programs are the practice of science, technology and art (IPTEKS) institutionalized by higher education through direct scientific methods to people who need to succeed in development and human development. Thematic Community service program (Thematic KKN) based on Problem Solving to solve problems with certain themes so that student activities are focused on solving certain problems and to achieve certain targets. One of them is the 105th Thematic KKN